Retrograde metamorphism in the Yamato Mountains, East Antarctica - Asami, Masao; Shiraishi, Kazuyuki (1985)
P(論文) Retrograde metamorphism which affected the granulite-facies garnetbiotite gneiss and calc-silicate gneiss from Massif A in the Yamato Mountains was petrographically revealed. In the garnet-biotite gneiss, the association of ferruginous matrix biotite (Type I biotite) and magnesian interior of zoned garnet is considered to show the preceded granulite-facies metamorphism because its (K_D)^ _<Mg-Fe> value (3.02) suggests an equilibrium temperature of 760℃. On the other hand, the association of magnesian biotite included in garnet (Type II biotite) and the enclosing ferruginous garnet and the association of magnesian biotite (Type III biotite) by which the garnet is partially embayed, fringed or veined and the contacting ferruginous garnet are supposed to show a retrograde metamorphism because their K_D values (about 6.61 and 9.41) suggest the temperatures around 520 and 450℃, respectively. In the calc-silicate gneiss, anorthite ((An)_<93>) is always enclosed by corona of Ca-garnet or Ca-garnet and quartz, and no anorthite contacts with wollastonite. This suggests stable coexistence of anorthite and wollastonite under the earlier granulite-facies metamorphic conditions, and later development of the corona as retrograde breakdown products. On the basis of experimental studies of the anorthite-wollastonite equilibria, and two-pyroxene and garnet-biotite thermometries, it is inferred that the granulite-facies metamorphism in the Yamato Mountains took place at about 750℃ and below 6kb. 700 and 500Ma ages known for the granulite-facies rocks from Massif A might be assigned to the granulite-facies and retrograde metamorphic events, respectively. The granulite-facies metamorphism in the Yamato Mountains can be chronologically correlated with the upper amphibolite-to granulite-facies metamorphism of medium-pressure type in the Prince Olav Coast-Lutzow-Holmbukta region, but the former metamorphism should have taken place at a higher crustal level than that in the latter region. departmental bulletin ...